Advances in Microbial Fermentation Processes - Tufariello, Maria; Grieco, Francesco (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book covedered high-quality contributions (original research articles or review papers) providing a picture on innovations in microbial fermentative processes, including improvements of quality/safety of fermented foods and beverages, production of high added-values products, and valorization/recovery of agro-food wastes.